Whole genome sequencing for the genetic diagnosis of heterogenous dystonia phenotypes. (December 2019) - Kumar, Kishore R.; Davis, Ryan L.; Tchan, Michel C.; Wali, G.M.; Mahant, Neil; Ng, Karl; Kotschet, Katya; Siow, Sue-Faye; Gu, Jason; Walls, Zachary; Kang, Ce; Wali, Gautam; et al.
Abstract: Introduction: Dystonia is a clinically and genetically heterogeneous disorder and a genetic cause is often difficult to elucidate. This is the first study to use whole genome sequencing (WGS) to investigate dystonia in a large sample of affected individuals. Methods: WGS was performed on 111 probands with heterogenous dystonia phenotypes. We performed analysis for coding and non-coding variants, copy number variants (CNVs), and structural variants (SVs). We assessed for an association between dystonia and 10 known dystonia risk variants. Results: A genetic diagnosis was obtained for 11.7% (13/111) of individuals. We found that a genetic diagnosis was more likely in those with an earlier age at onset, younger age at testing, and a combined dystonia phenotype. We identified pathogenic/likely-pathogenic variants in ADCY5 (n = 1), ATM (n = 1), GNAL (n = 2), GLB1 (n = 1), KMT2B (n = 2), PRKN (n = 2), PRRT2 (n = 1), SGCE (n = 2), and THAP1 (n = 1). CNVs were detected in 3 individuals. We found an association between the known risk variant ARSG rs11655081 and dystonia (p = 0.003). Conclusion: A genetic diagnosis was found in 11.7% of individuals with dystonia. The diagnostic yield was higher in those with an earlier age of onset, younger age at testing, and a combined dystonia phenotype. WGS may be particularly relevant for dystonia given that it allows for the detection of CNVs, which accounted for 23% of the genetically diagnosed cases. Highlights: Whole genome sequencing (WGS) offers potential advantages over whole exome sequencing or gene panels for testing in dystonia. A genetic diagnosis was found in 13/111 (11.7%) of individuals with dystonia in this study using WGS. The diagnostic yield was higher with an earlier age of onset, younger age at testing, and combined dystonia phenotype. WGS is better at detecting clinically relevant sequencing variants in dystonia genes in comparison to WES. WGS can detect copy number variants in dystonia genes, which accounted for 3/13 (23%) individuals with a genetic diagnosis.